IMPROVEMENT OF THE AUDITING MECHANISM OF THE LABOR SAFETY MANAGEMENT SYSTEM (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The purpose of this article is to propose to transform the internal audit system, in particular, labor protection audit in general and to unlock its potential. The article proposes an improved audit mechanism and the transformation of the inspection system into audit systems with the division of audits into three independent and at the same time complementary directions: internal, external and state audit.